An Initial Experience of Cochlear Implantation for Patients With Single-Sided Deafness After Prior Osseointegrated Hearing Device. Issue 1 (January 2015) - Erbele, Isaac D.; Bernstein, Joshua G. W.; Schuchman, Gerald I.; Brungart, Douglas S.; Rivera, Arnaldo
<x xml:space="preserve">Abstract</x> Objective To compare preoperative and postoperative sound localization and surgical outcomes in patients with a history of osseointegrated hearing device (OHD) placement who underwent cochlear implantation for severe to profound sensorineural hearing loss in one ear and normal cochlear function in the contralateral ear (single-sided deafness [SSD]). Study Design Case series. Study Setting Tertiary care center, cochlear implant (CI) program. Patients Five patients with a previously placed OHD, implanted at our institution between late 2012 and late 2013, who were undergoing cochlear implantation to address SSD. Causes of their initial SSD included iatrogenic sudden sensorineural hearing loss, and perilymphatic fistula. Indications for cochlear implantation included a desire for binaural hearing, surgical treatment for tinnitus, and staging for treatment of contralateral conductive hearing loss. Interventions Cochlear implantation; intraoperative and postoperative antibiotics. Main Outcome Measures Accuracy of sound localization for environmental sounds presented in a mixture for three device conditions: monaurally with the acoustic hearing ear only, OHD in addition to the acoustic hearing ear, and CI in addition to the acoustic hearing ear. Complications. Continued use of CI. Results Modestly improved sound localization with CI compared with monaural listening or listening with an OHD (p < 0.0001). Wound dehiscence and infection with our first two patients; none with the use of perioperative and postoperative antibiotics (three patients). Four patients continued to use their CI for at least 4 months after activation (mean, 13 mo) and expressed satisfaction with the device; one was lost to follow-up. Conclusion Cochlear implantation for this population of patients produced modestly improved localization accuracy, and most patients expressed satisfaction with this intervention. In this series of cochlear implantation after OHD, our first two patients had wound infection and dehiscence. We recommend perioperative and postoperative antibiotics to prevent this complication.